Knowledge Level in Cleaning Services regarding Government Regulations and the Dangers of Smoking - Bryan Anna Wijaya; Fiona Valencia Setiawan (Lembaga Pengembangan Kinerja Dosen, 2024)
ABSTRACT Cigarette consumption is one of the main risk factors that can cause various non-communicable diseases, such as coronary heart disease, stroke, lung cancer, and even death. In a cigarette, there are around 70 substances that can cause cancer and contain more than 5,000 chemicals that can have a negative impact on health. In Indonesia, cigarette consumption is regulated by the Republic of Indonesia Government Regulation Number 109 of 2012 concerning the Safeguarding of Materials Containing Addictive Substances in the Form of Tobacco Products for Health. In chapter IV, the fifth section, Articles 49-52 regulate non-smoking areas where someone cannot consume cigarettes in non-smoking areas. This research is descriptive research with survey methods and sample collection using purposive sampling from Tarumanagara University cleaning service with a sample size of 108 respondents. As many as 67.6% of respondents were male and 71.3% were active smokers. Conclusion: most respondents (78.8%) had good knowledge about the dangers of smoking and as many as 89.8% were aware of government regulations governing cigarette consumption